Seismic Analysis of Multistory Building with Stub Column - Jain, Pankaj; Dogra, Manish (Journal of Advance Research in Mechanical and Civil Engineering (ISSN: 2208-2379), 2016)
In present scenario buildings with Stub column is a typical feature in the modern multistory construction in urban India. Such features are highly undesirable in building built in seismically active areas. This study highlights the importance of explicitly recognizing the presence of the Stub column in the analysis of building. Alternate measures, involving stiffness balance of the first story and the story above, are proposed to reduce the irregularity introduced by the Stub columns. FEM codes are developed for 2D multi story frames with and without Stub column to study the responses of the structure under different earthquake excitation having different frequency content keeping the PGA and time duration factor constant. The time history of floor displacement, inter story drift, base shear, overturning moment are computed for both the frames with and without Stub column.